2023
DOI: 10.3233/bmr-210374
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short foot exercises to treat flat foot deformity: A systematic review

Abstract: BACKGROUND: Studies on the effects of performing short foot exercises (SFEs) on the medial longitudinal arch (MLA) have been inconclusive. OBJECTIVE: This study aimed to conduct a systematic review of the effects of SFEs. METHODS: ‘SFE’ and ‘intrinsic foot muscle’ were keywords used to search for randomized controlled trials. One researcher screened relevant articles based on their titles and abstracts, and two independent researchers closely read the texts, accepting nine studies for inclusion. Outcomes, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
0
11
0
2
Order By: Relevance
“…17 The results of the present study were also supported by Hara et al who found that ≥ five weeks of SFE was effective in improving the MLA. 18 The plantar fascia is a major supporter of MLA retention. 22 It overlaps the intrinsic foot muscles and connects to the flexor digitorum brevis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The results of the present study were also supported by Hara et al who found that ≥ five weeks of SFE was effective in improving the MLA. 18 The plantar fascia is a major supporter of MLA retention. 22 It overlaps the intrinsic foot muscles and connects to the flexor digitorum brevis.…”
Section: Discussionmentioning
confidence: 99%
“…3 As a result, this increases the height of the MLA. 16,18 Several previous studies investigated the effects of SFE on the MLA. 18 Some studies demonstrated the presence of a flatfoot deformity resulting in an increased Q-angle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value obtained by measuring the width of the middle foot of the foot print compared to the width of the metatarsal bone is the Chippaux-Smirak Index. BMI obtains the height and weight through physical examination of the patient, and calculates the height ÷ weight 2 The resulting value is BMI. Knee joint Q angle: (The angle from the midpoint of the patella to the tibial tubercle that intersects the traction line of the quadriceps femoris is called the Q angle) When the patient stands in a neutral position, mark the positions of the anterior superior iliac spine, the midpoint of the patella, and the tibial tubercle, and then measure the Q angle.…”
Section: Methodsmentioning
confidence: 99%
“…Most patients are accompanied by anterior foot abduction and calcaneal valgus. 1,2 Adolescent flat foot are mostly flexible and flat foot, with arches that are not fully formed during development and relatively high joint activity. Most adolescent flat foot will return to normal as they age, and some patients will develop into adult flat foot.…”
mentioning
confidence: 99%